Study on Impact Behavior and Impact Force of Bridge Pier Subjected to Vehicle Collision - Deyuan Zhou; Ruiwen Li; Juan Wang; Changtuan Guo (Shock and Vibration)
The increasing occurrence of vehicle-pier collision accidents has significant influences on the safety of bridge structures. In order to study the impact behavior of bridge piers, a vehicle-double-pier collision numerical model was developed by LS-DYNA. Nonlinear material constitutive laws considering the strain-rate effect were used. The reliability of numerical analyses was validated. Parametric studies were carried out to investigate the effects of impact velocity, impact mass, and concrete and steel strength on the impact behaviors of piers and the impact forces. The relationship between failure modes of the impacted piers and impact energy was analyzed. Based on the numerical analysis results, the current impact design provisions of AASHTO, Eurocode, and JTG D60 were found to be unconservative, which could result in that piers designed with the current standard codes were vulnerable to the large impact energy. The recommended value of equivalent static force in the current standards is unreasonable.